Promising Directions of Cooperation Among Eurasian Economic Union Countries - Yurievna Myasnikova, Olga; Ivanovna Shatalova, Irina; Vyacheslavovna Zenkina, Elena; Vyacheslavovna Bogacheva, Tatyana; Igorevich Illeritsky, Nikita; Muradovna Kutlyeva, Gozelâ€™ (International Journal of Engineering and Technology, 2018)
The paper explores the possibilities of technological cooperation among the countries of the Eurasian Economic Union (officially EAEU, but sometimes called EEU or EAU). Based on specific and individual backgrounds of each EAEU country, the promising areas for its expansion are determined within the framework of industries with export potential, high-technological, oriented at national markets for the formation of an economic strategy focused on regional integration with the highest level of encouragement of the national economic interests of the EAPC countries. The most significant sectors of the economy are identified: the space industry, energy, metallurgy, engineering, agriculture, etc. The feasibility of value chain development in the region was highlighted, as well as the development of inter-industry and intra-sector cooperation with partner countries in strategically important sectors of the economy, which includes the opportunity of forming specific sectoral niches through specialization and development of national industrial potential of the member states. This focus will promote development and realization of internal scientific and technical potential of the EAEU countries, commercialization of R&D results, technological improvements and will increase their competitiveness on the global markets.Â Â